逆向法选择渐开线齿轮的变位系数 - 赵振江 (Jixie chuandong)
A new kind of method for the choice of gear modification coefficients is presented.Its main idea is regard gear modification coefficient as a known parameter.The method take full advantage of a computer’s features of quick operation and accurate calculation and judgement function.A computer can find modification coefficients from a lots of modification coefficients which meet the needs of given condition,in the same time user needs input all kinds of given parameters and limited conditions only.